Life Beyond Clickbait Journalism: A Transnational Study of the Independent Football Magazine Market. (August 2021) - Ramon, Xavier; Tulloch, Christopher D.
In a cluttered and increasingly complex environment characterized by the multiplication of platforms, a constellation of quality football print magazines has emerged as an alternative destination in sports journalism. To trace the expansion of the independent football magazine market, in-depth interviews were conducted with the editors of eight prestigious projects from seven countries: Howler (United States), Panenka and Líbero (Spain), Mundial (United Kingdom), So Foot (France), 11 Freunde (Germany), Offside (Sweden), and Ballesterer (Austria). Independent football magazines position themselves as part of a journalistic counteroffensive to the metric-driven, routinized, and complacent approach that currently shapes mainstream sports media output. In contrast to the primary orientation of sports journalism towards economic capital, their editorial philosophy is built on three core axes aimed at developing cultural capital: (1) a diverse and multifaceted football agenda that embraces unheard voices and far-reaching issues of a sociocultural, geopolitical, and economic nature; (2) the importance of dedicating time and resources to create a visually distinctive output; and (3) a deliberate emphasis on nostalgia and resistance to the seemingly endless commodification of football. As part of their creative approach, gathering and nourishing a community of readers has been fundamental to the growth and sustainability of those projects.